1996
DOI: 10.1111/j.1365-3091.1996.tb01455.x
|View full text |Cite
|
Sign up to set email alerts
|

The stability of sublittoral, fine‐grained sediments in a subarctic estuary

Abstract: The erodibility of natural estuarine sediments was measured in situ along a longitudinal transect of Manitounuk Sound, Hudson Bay, using the benthic flume Sea Carousel. Sedimentation processes along the transect varied from continuous, rapid, post-glacial sedimentation in the inner Sound, to glacial outcrops and seabed reworking of the outer Sound. The grain size and physical bulk properties reflect changes in depositional environment and correlate with sediment erosion threshold stress (TJ, erosion rate (E), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…3), with maximum concentrations (c.a., 320-380 mg l -1 ) measured at T5 and T10 after the highest TSS had been applied. These SPM:shear stress relationships are similar in shape to those reported in the Tamar Estuary (Bale et al, 2006) and other muddy estuaries (Amos et al, 1996;Widdows et al, 2004).…”
Section: Mini-annular Flume Simulationssupporting
confidence: 80%
“…3), with maximum concentrations (c.a., 320-380 mg l -1 ) measured at T5 and T10 after the highest TSS had been applied. These SPM:shear stress relationships are similar in shape to those reported in the Tamar Estuary (Bale et al, 2006) and other muddy estuaries (Amos et al, 1996;Widdows et al, 2004).…”
Section: Mini-annular Flume Simulationssupporting
confidence: 80%
“…The value of 10 min was used in order to homogenize the results (Hydraulics Research Station, 1980; Amos et al, 1996). Laws for individual deployments have determination coefficient (r 2 ) range between 0.67 and 0.94 but a composite law would have a r 2 of only 0.58 (Moreau et al, 2003):…”
Section: Definition Of the Erosion Potentialmentioning
confidence: 99%
“…Rhoads, 1974;Yingst and Rhoads, 1978;Nowell et al, 1981;Grant and Gust, 1987;Paterson, 1989). Several studies have demonstrated that bacteria, benthic diatoms and some macrozoobenthic organisms may modify the erosion threshold of soft-bottom substrata (Paterson, 1989;Underwood and Paterson, 1993;Yallop et al, 1994;Austen et al, 1999;Tolhurst et al, 1999) and some have also attempted to quantify erosion rates of cohesive sediments (Amos et al, 1992(Amos et al, , 1996(Amos et al, , 1997Sutherland et al, 1998;Willows et al, 1998;Andersen, 2001a).…”
Section: Introductionmentioning
confidence: 99%